Breakfast of biodiversity. The truth about rain forest destruction / John Vandermeer - Vandermeer, John (1995)
Slicing up riain Forrest on your breakfast cereal, costa Ricans and their love/hate of bananas, loggers, farmers, and banana companies, a rich history; the rain forest is neither fragile nor stable, the rain forest, stable web or fragile house of cards, six key factors in rain forest function; farming on rain forest soils, rain forest landscapes, the invisible mosaic, slash-and burn agriculture, stabilizing agriculture on rain forest soils, some models for the future; the political economy of agriculture in rain forest areas, the origin and intensification of agriculture, agriculture and enclave production; the multiple faces of agriculture in the modern world system, the modern world sytem, agriculture in the developed world today; the political ecology of logging and related activities, reforestation and tropical plantations; rain forest conservation, the direct or indirect approach, the sarapiqui revisited, by contrast, the costa Rica, Nicaragua; biodiversity, of agriculture, and rain forest, biodiversity and utilitarianism, biodiversity and agriculture; who constructs the rain forest, the nature of preserving nature; past causes, future models, present action, the web of causality, the planned mosaic, the political action plan